Research on Performance Test of Reducer based on JUCE Library - Liangliang Yang; Liangzhu Qian; Xiufeng Wang (Jixie chuandong)
Taking the reducer for robot as the research object，a reducer test device composed of drive system，mechanical system，control system and data acquisition system is developed to test its mechanical transmission performance. In the process of testing，because of the traditional test method is difficult to capture the instantaneous change of the data，this is not conducive to the study of precision gear reducer. In order to solve this problem，the solving method is put forward. The software system based on JUCE libraries is designed，combined with the movement control cards of data transmission，the performance test of speed reducer is finished. The results show that the test system can quickly and accurately measure the transmission performance of the reducer，and it is expected to analyze and optimize to improve the overall performance of the reducer.